Obtención de u insecticida biológico a partir de la Higuerilla (Ricinus communis), Machala 2014 - Ramos Jaramillo, Elvis G. (2015)
The objective of this research was to develop a safe natural insecticide active components from the seed of the castor plant to control cockroaches, flies and mosquitoes common (Aedes Aegypt), in order, that is for health of people and biodegradable. The methodology implied performing three insecticide formulations at three different concentrations, for which the seeds of castor was used when they were at optimum ripeness, were ground and mesclaron with purified water for an hour to reach the desired concentrations (5, 10 and 15%). The result of the characterization chromatographic (GC / MS) castor seed indicates that 45% is composed of ricinoleic acid oil (89%), propanoic acid, 2-oxy (3.34%), glycerol (3.34 %), linoleic acid (3.34%), Trans-2,8-dimethyl-1,1-bis (methylthio) -2-Phenyl-1,2-diidroazeto (2,1-b) quinazoline (6.68 %) and stearic (3.34%) acid, the latter gives the surfactant owned oil that can be mixed with water (Rosen & Kunjappu, 2012). The test insects indicates that the concentration if you have significant effect (p <0.05) in eliminating cockroaches, the more concentrated the largest number of dead cockroaches in less time, the biopesticide that differs from the two lower concentrations is 15 % extract of castor, while for flies and mosquitoes bioinsecticide using a concentration of 5% is needed. In conclusion if the elimination of cockroaches, flies and mosquitoes using biopesticide made from castor seeds is possible.